Return, Circular, and Onward Migration Decisions in a Knowledge Society - Amelie F. Constant (Center for Economic Studies and ifo Institute (CESifo), 2019)
This chapter provides a state-of-the-art literature review about research that aims to explain the return, repeat, circular and onward migration of the highly-skilled migrants around the world. After it describes the status quo in the knowledge economy and the international race for talent, it presents the relevant theories and concepts of migration in the social sciences and how these theories accommodate the phenomena of return, repeat and onward migration. A special section is devoted to selection. The chapter then summarizes, evaluates, and juxtaposes existing empirical evidence related to theoretical predictions. Observables such as education, income, gender and home country as well as unobservables such as ability, social capital and negotiating skills play a strong role in influencing return, repeat and onward migration decisions. Yet, there is no consensus on the direction of the effect. The chapter discusses shortcomings and limitations along with policy lessons. It concludes by highlighting holes in the literature and the need for better data.
Keywords: F22; J15; J18; J20; J61; 330; return; circular; onward; international labor migration; knowledge economy; high-skilled; public policy